2009
DOI: 10.1101/gr.094987.109
|View full text |Cite
|
Sign up to set email alerts
|

A method for rapid, targeted CNV genotyping identifies rare variants associated with neurocognitive disease

Abstract: Copy-number variants (CNVs) are substantial contributors to human disease. A central challenge in CNV-disease association studies is to characterize the pathogenicity of rare and possibly incompletely penetrant events, which requires the accurate detection of rare CNVs in large numbers of individuals. Cost and throughput issues limit our ability to perform these studies. We have adapted the Illumina BeadXpress SNP genotyping assay and developed an algorithm, SNP-Conditional OUTlier detection (SCOUT), to rapidl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
99
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 39 publications
7
99
0
1
Order By: Relevance
“…It has been hypothesized that this deletion can predispose individuals to a variety of neurocognitive disabilities, including the developmental delay and seizures present in this subject. 27,29,30 This deletion may contribute to the resulting phenotype in this proband along with the duplication of NF1, consistent with a "two-hit" model recently proposed to explain phenotypic variability and reduced penetrance with recurrent 16p12.1 microdeletions 41 and hypothesized to hold true for other genomic disorders. 42 In other individuals, the phenotype may be impacted by environmental, genetic, or epigenetic variants that are undetectable by aCGH.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It has been hypothesized that this deletion can predispose individuals to a variety of neurocognitive disabilities, including the developmental delay and seizures present in this subject. 27,29,30 This deletion may contribute to the resulting phenotype in this proband along with the duplication of NF1, consistent with a "two-hit" model recently proposed to explain phenotypic variability and reduced penetrance with recurrent 16p12.1 microdeletions 41 and hypothesized to hold true for other genomic disorders. 42 In other individuals, the phenotype may be impacted by environmental, genetic, or epigenetic variants that are undetectable by aCGH.…”
Section: Discussionsupporting
confidence: 85%
“…This deletion has been implicated as a risk factor for a variety of neurocognitive disorders including behavioral problems and idiopathic generalized epilepsy. [27][28][29][30][31] It is often inherited from a normal or mildly affected parent and has also been seen in normal control individuals. 27,28,30,31 Additional clinically significant copy-number alterations were not identified in any of the remaining subjects.…”
Section: Results Molecular Analysismentioning
confidence: 99%
“…Microdeletions of 15q11.2 region have also been reported in cases with delayed motor and speech development, autism, obsessive-compulsive disorder, and dysmorphic features without Prader-Willi/Angelman syndrome, suggesting HI for TUBGCP5, CYFIP1, NIPA2, and NIPA1. 35 Although observed in control individuals, the role of 15q11.2 duplications is yet to be unravelled. (iv) CTNND2 446 bp duplication in case P036.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40][41] More recent studies have demonstrated additional rare variant influences on the pathogenesis of a variety of complex diseases and traits such as type 1 diabetes, colorectal cancer, plasma lipoprotein levels and neurological disorders. [42][43][44][45][46][47][48][49] Screening candidate genes in groups of patients for germline variation is the first step in unraveling rare variation, a step that is already being made much easier by the increasing accessibility of nextgeneration sequencing technologies. However, functional studies of the most interesting variants must follow closely.…”
Section: Discussionmentioning
confidence: 99%